Conjugation, labelling and in vitro/in vivo assessment of an anti-VEGF monoclonal antibody labelled with niobium isotopes - De La Fuente, A; Radchenko, V; Tsotakos, T; Tsoukalas, C; Paravatou-Petsotas, M; Harris, AL; Köster, U; Rösch, F; Bouziotis, P (Springer Nature, 2018)
Niobium-90 (90Nb) is a positron emitting radionuclide that exhibits attractive characteristics for use in the design and synthesis of radioimmunoconjugates. In the current study we have investigated 90Nb as a possible future isotope for immuno-PET. Prior to 90Nb in vivo studies, this paper describes in vitro and ex vivo studies using a Niobium-95 (95Nb)-monoclonal antibody analogue. 95Nb has a half-life of 35 days and is convenient for long-term studies. 95Nb-labelled bevacizumab was evaluated for early antiangiogenic tumor response assessment and the results were compared with other well established PET nuclides for immuno-PET. 95Nb was quantitatively recovered (> 95%) from irradiated natural Zr in a multistep separation. Bevacizumab was modified with the Df-Bz-NCS (Df) chelate and labelled with previously separated 95Nb. Stability of 95Nb-Df-bevacizumab was evaluated in saline and in human plasma over 7 days presenting > 96% and > 94% of intact product, respectively. Biodistribution ex vivo studies were performed on M165 tumor-bearing mice. 95Nb was obtained in high purity (99.999%) and high radioactivity concentration (1.7 MBq/µL) in a total volume of 200 µL oxalic acid (0.1 M), ready for labelling. Df-bevacizumab labelling was efficient (> 95%) and in vitro stability of 95Nb-Df-bevacizumab was high. Ex vivo studies displayed good tumor-to-background ratios, optimum after 2 days p.i., after iv injection of 20 µg of antibody per mouse. 95Nb was successfully produced and purified from the irradiated target. Labeling of bevacizumab pre-modified with desferrioxamine was achieved in high yields. After in vitro stability of 95Nb-Df-bevacizumab was demonstrated, ex vivo biodistribution studies showed specific tumor uptake in M165 tumor-bearing mice. Consequently, in vivo studies with 90Nb-Df-bevacizumab and small animal PET are in preparation, and we expect that 90Nb-Df-conjugated antibodies will show potential for immuno-PET.